2011
DOI: 10.1039/c1cc11827g
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric pyrene derivatives for organic field-effect transistors

Abstract: For the synthesis of an ortho-dithienylpyrene, a K-region bromination of pyrene was developed which enabled the first reported, non-statistical asymmetric functionalization of pyrene at the 4, 5, 9 and 10 positions. Crystal structures, optical and electronic properties and FET characteristics have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 25 publications
(26 reference statements)
1
85
0
Order By: Relevance
“…al. 10 have developed an asymmetric functionalization method to direct bromine atoms to the K-region without the need for tert-butyl groups. Additionally, in our laboratory, we also reported the selective formation of the 5-mono-and 5,9-di-substitution products from 7-tert-butyl-1,3-dimethylpyrene by formylation and acetylation depending on the type of Lewis acid catalyst deployed.…”
mentioning
confidence: 99%
“…al. 10 have developed an asymmetric functionalization method to direct bromine atoms to the K-region without the need for tert-butyl groups. Additionally, in our laboratory, we also reported the selective formation of the 5-mono-and 5,9-di-substitution products from 7-tert-butyl-1,3-dimethylpyrene by formylation and acetylation depending on the type of Lewis acid catalyst deployed.…”
mentioning
confidence: 99%
“…On the other hand, we achieved the synthesis of the oxoborolanes [2,5-bisoxoborolanethiophene (10) and 5,5 0 -bisoxoborolane-2,2 0 -bithiophene (11)]. First, we prepared the brominated compounds 2,5-dibromothiophene and 5,5 0 -dibromo-2,2 0 -bithiophene, using NBS as a source of bromine.…”
Section: Resultsmentioning
confidence: 99%
“…227-231 C). (11). First 5,5 0 -dibromo-2,2 0 -bithiophene was synthesized, using a bromination procedure similar to that described for the previous compound.…”
Section: Synthesis Of Monomers and Oligomers (Terthiophenes And Quatementioning
confidence: 99%
See 1 more Smart Citation
“…[17] Recently, we reported that the treatment of compound 2 with N-bromosuccinimide (NBS) in concentrated sulfuric acid at room temperature gives 4,5-dibromo-9,10-diketopyrene 3 in quantitative yield. [18] This key step opens the way to a whole series of 4,5-versus 9,10-substituted pyrene derivatives. As our interest lies in the introduction of solubilizing groups, reductive alkylation was achieved using alkyl bromides in the presence of sodium dithionite.…”
Section: Synthesismentioning
confidence: 99%